Dependency, trust and choice? Examining agency and 'forced options' within secondary-healthcare contexts. (September 2015) - Brown, Patrick R; Meyer, Samantha B
This article seeks to extend understandings of the ways in which trust is integral to analysing 'choice' within healthcare contexts, while also reappraising choice and its salience for grasping the nature of trust. Interrogating processes of 'choosing to trust', the authors describe various mechanisms through which 'decisions' are constrained while emphasising enduring agency to (dis)trust, even amid contexts where choice would appear annihilated by patients' vulnerability. Drawing initially on Greener, Luhmann and Giddens, the article develops an analysis of how features of vulnerability, time and consciousness function in bounding choices and trust. Multiple structurations of choosing and trusting, alongside continuing agency, help further illuminate various power dimensions within clinical encounters. This theoretical analysis is illustrated using qualitative interview data from two studies across contrasting service settings in Australia and England, enabling recognition of further system and contextual influences upon patients' vulnerability, dependency and trust, as these characterise processes of 'choice'.